2018
DOI: 10.1097/j.pain.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

Use of prescription opioids before and after an operation for chronic pain (lumbar fusion surgery)

Abstract: Lumbar fusion surgery is usually prompted by chronic back pain, and many patients receive long-term preoperative opioid analgesics. Many expect surgery to eliminate the need for opioids. We sought to determine what fraction of long-term preoperative opioid users discontinue or reduce dosage postoperatively; what fraction of patients with little preoperative use initiate long-term use; and what predicts long-term postoperative use. This retrospective cohort study included 2491 adults undergoing lumbar fusion su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 29 publications
5
59
0
Order By: Relevance
“…Indeed, prior to lumbar fusion surgery, over 90% of patients surveyed considered continued dependence on opioids neither an expected nor acceptable outcome. 34 In a retrospective cohort study of 2,492 patients having lumbar fusion surgery for degenerative conditions, including LSS, Deyo et al 35 found that more patients received long-term opioids postoperatively (n=1,094) than preoperatively (n=1,045). Additionally, opioid-naïve patients had a substantial risk of initiating long-term use.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior to lumbar fusion surgery, over 90% of patients surveyed considered continued dependence on opioids neither an expected nor acceptable outcome. 34 In a retrospective cohort study of 2,492 patients having lumbar fusion surgery for degenerative conditions, including LSS, Deyo et al 35 found that more patients received long-term opioids postoperatively (n=1,094) than preoperatively (n=1,045). Additionally, opioid-naïve patients had a substantial risk of initiating long-term use.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative opioid use was found to be the strongest predictive factor in some studies, with 71%-77% of preoperative opioid users continuing at 6-7 months postoperatively (Bartels, Fernandez-Bustamante, McWilliams, Hopfer, & Mikulich-Gilbertson, 2018;Deyo et al, 2018;Rozet et al, 2014). Further, surgery itself may result in or worsen chronic pain for some patients.…”
Section: Preoperative Opioid Usementioning
confidence: 99%
“…Further, surgery itself may result in or worsen chronic pain for some patients. Deyo et al (2018) found that lumbar fusion surgery infrequently eliminated the use of long-term opioids, with 44.8% of preoperative opioid users requiring higher dose postoperatively. Among opioid-naive preoperative patients, 12.8% became long-term opioid users after lumbar fusion.…”
Section: Preoperative Opioid Usementioning
confidence: 99%
“… 16 The predictive value of prior opioid use on future opioid use is well established in surgical cohorts. 9 , 17 - 19 Work has also been done to identify rates and predictors of opioid use for many conditions including musculoskeletal pain in non-surgical primary care settings. 20 However, outside of low back pain, 21 we have not found any investigation into the predictive value of prior opioid use for future opioid use in non-surgical and non-cancer pain cohorts.…”
Section: Introductionmentioning
confidence: 99%